2019
DOI: 10.1111/jce.13956
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of the electrocardiogram and the intracardiac electrogram in left bundle branch pacing

Abstract: Introduction: Left bundle branch pacing (LBBP) has recently been reported to maintain left ventricular electrical synchrony with a low and stable threshold. However, the electrocardiogram (ECG) definitions of LBBP have not been well established. We report four cases to show the characteristics of the ECG and the intracardiac electrogram (EGM) in LBBP. Methods and Results: Four patients, two with an atrioventricular block (AVB) and two with left bundle branch block (LBBB), were included in the study. LBBP was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
124
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(134 citation statements)
references
References 17 publications
8
124
0
2
Order By: Relevance
“…In 2017, Huang et al 7 first reported left bundle branch pacing (LBBP), which is a transvenous, trans‐septal implantation technique resulting in left bundle branch (LBB) capture with low capture thresholds. Recent studies demonstrated the feasibility and effectiveness of LBBP in patients indicated for ventricular pacing and cardiac resynchronization therapy 8–10 . We previously found the LBB COI in a patient with atrial fibrillation, 11 however, there have been no systematic studies on the COI with leads implanted at the LBB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, Huang et al 7 first reported left bundle branch pacing (LBBP), which is a transvenous, trans‐septal implantation technique resulting in left bundle branch (LBB) capture with low capture thresholds. Recent studies demonstrated the feasibility and effectiveness of LBBP in patients indicated for ventricular pacing and cardiac resynchronization therapy 8–10 . We previously found the LBB COI in a patient with atrial fibrillation, 11 however, there have been no systematic studies on the COI with leads implanted at the LBB.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated the feasibility and effectiveness of LBBP in patients indicated for ventricular pacing and cardiac resynchronization therapy. [8][9][10] We previously found the LBB COI in a patient with atrial fibrillation, 11 however, there have been no systematic studies on the COI with leads implanted at the LBB. Unlike HBP where the target zone is small, the LBB fibers are widely distributed as a subendocardial network, 12,13 and it may be easier to reach the LBB area.…”
Section: Introductionmentioning
confidence: 99%
“…Since it was initially described by Huang in 2017, 1 left bundle branch area pacing (LBBAP), a novel form of physiological pacing, has been increasingly adopted in clinical practice, with growing evidence demonstrating its feasibility and potential clinical benefits. [2][3][4][5][6][7][8] It is widely recognized that the surface electrocardiogram (ECG) during LBBAP generally presents a right bundle branch block (RBBB) pat-tern, as a result of early penetration of the electrical impulse into the left bundle branch (LBB) conduction system and a delay in right ventricular (RV) activation. However, differences in ECG characteristics between LBBAP and native RBBB have not been systematically compared.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various physiological pacing strategies that are available, LBBP has been applauded as a feasible strategy for patients with heart failure, especially for those who failed in traditional BiV or His bundle pacing (HBP) 12 . Initial investigation also confirmed the safety and feasibility of LBBP during short‐term and medium‐term follow‐ups 7,8,13‐16 . Although a previous study demonstrated that the electric parameters remained stable within a mean follow‐up duration of 3 months, 17 only few studies have investigated the intermediate‐term outcomes of this new technique named LBBP.…”
Section: Discussionmentioning
confidence: 99%